Identifying and prioritizing appropriate strategies for customer loyalty in a mass environment (case study: clothing house) - Zahra Joorbonyan; Ali Sorourkhah; Seyyed Ahmad Edalatpanah (تصمیم گیری و تحقیق در عملیات)
Purpose: In a competitive environment where business competition has become a fundamental challenge for managers, various ways to maintain, survive, or grow the organization are conceivable. Among these, marketing experts believe that customer loyalty is one of the most effective tools in facing this challenge. To achieve customer loyalty, various and diverse strategies have been mentioned in the literature by researchers and experts, which organizations can use, depending on the conditions, one or a combination of them. In such circumstances, managers usually have several strategies and must choose the most appropriate one(s). The present study aims to provide a combined approach for prioritizing customer loyalty strategies.Methodology: This research uses a matrix-based approach to robustness analysis, which can deal with complexity and uncertainty. The proposed algorithm combines it with strategic planning tools (strategies derived from strategic objectives and SWOT analysis) for prioritizing and selecting strategies. The proposed approach was implemented in a case study on prioritizing customer loyalty strategies for a women's clothing boutique in Ramsar City. Available strategies, influential environmental variables, definitions of future scenarios, and the performance of strategies in different environmental conditions were determined based on the judgments of the problem owner.Findings: The results showed that considering influential environmental variables (national currency value, market access and raw materials, lifestyle changes, investment security, government-private sector relations, and the speed of technological change), supplier selection, contractor selection, and attracting a sponsor have the highest priority strategies. Afterwards, environmental advertising, collaborative production, and customer relationship management were placed in subsequent rankings. The outputs of the proposed approach indicate that considering the country's foreseeable future conditions, higher-priority strategies minimize environmental risks and their impact on the business.Originality/Value: The problem of choosing a customer loyalty strategy is a decision-making problem that can be addressed with the help of decision-making knowledge. However, the literature suggests that classical strategic planning approaches Quantitative Strategic Planning Matrix (QSPM) or multi-criteria Decision-Making Approaches (MCDM) are used in most cases of such decision-making. Despite their capabilities and features, these approaches face challenges in dealing with variable and evolving conditions (future uncertainty). An alternative approach, robustness analysis, can consider alternative futures but cannot define available strategies. Based on this, combining the matrix approach to robustness analysis with classical strategic planning approaches will be a response to the above problem.